Legal Implications of Joint Property Control by the Second Wife in Inheritance Disputes Islamic Law Perspective - Akbar, Muhamad Haidir; Angga, La Ode; Latupono, Barzah (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Inheritance disputes in polygamous families often lead to conflict, especially when the second wife controls all the inheritance without a fair division to the first wife and her children.Purposes of the Research: The purpose of this study is to find out the procedure for distributing inheritance to the first and second wives in accordance with Islamic principles, as well as to find out the legal consequences for the joint property of the first wife that is controlled by the second wife.Methods of the Research: This research uses a normative juridical method with a legislative and conceptual approach, and is analyzed qualitatively. The data sources come from literature studies, legal literature, laws and regulations, and the Compilation of Islamic Law.Findings of the Research: The procedure for distributing inheritance to the heirs of the deceased husband begins with identifying the inheritance, including inheritance and joint property, then deducting debts, funeral expenses, and wills, before being distributed to the heirs according to fariath. As a result of the law of the joint property of the first wife which is controlled by the second wife, without a valid legal basis, it is contrary to the principle of justice in Islam and can be considered as an act of ghasab (deprivation of rights). Wives in polygamous marriages are only entitled to joint property acquired during their respective marriages. Therefore, the second wife is not entitled to control the property that is the result of the husband's marriage to the first wife. Such possession can give rise to the obligation to restore rights, trigger inheritance conflicts, and lawsuits from other heirs.